"Near Miss" Obstetric Events and Maternal Deaths in a Tertiary Care Hospital: An Audit. (26th June 2013) - PS, Roopa; Verma, Shailja; Rai, Lavanya; Kumar, Pratap; Pai, Murlidhar V.; Shetty, Jyothi
Abstract : Objectives . (1) To determine the frequency of maternal near miss, maternal near miss incidence ratio (MNMR), maternal near miss to mortality ratio and mortality index. (2) To compare the nature of near miss events with that of maternal mortality. (3) To see the trend of near miss events. Design . Audit. Setting . Kasturba Hospital, Manipal University, Manipal, India. Population . Near miss cases & maternal deaths. Methods . Cases were defined based on WHO criteria 2009. Main Outcome Measures . Severe acute maternal morbidity and maternal deaths. Results . There were 7390 deliveries and 131 "near miss" cases during the study period. The Maternal near miss incidence ratio was 17.8/1000 live births, maternal near miss to mortality ratio was 5.6 : 1, and mortality index was 14.9%. A total of 126 cases were referred, while 5 cases were booked at our hospital. Hemorrhage was the leading cause (44.2%), followed by hypertensive disorders (23.6%) and sepsis (16.3%). Maternal mortality ratio (MMR) was 313/100000 live births. Conclusion . Hemorrhage and hypertensive disorders are the leading causes of near miss events. New-onset viral infections have emerged as the leading cause of maternal mortality. As near miss analysis indicates the quality of health care, it is worth presenting in national indices.